Funcionalidade da via auditiva em nível de tronco encefálico em indivíduos jovens com e sem queixa de compreensão de fala. - Silva, Débora Durigon da (2016)
Introduction: Among the different hearing functions, is to allow the individual to understand the speech sounds, from the capture and processing of what is heard. For this reason, understanding how sound is captured and encoded by the central auditory pathway becomes paramount, because it is not sufficient to comprehend exclusively the competencies of the peripheral pathways. From that comes the importance of the investigation via auditory evoked potentials and behavioral examinations of auditory processing. Objective: To investigate the auditory pathways functionality in brainstem level through the Brainstem Auditory Evoked Potentials with speech stimuli in both individuals presenting or not complaints of speech comprehension and behavioral tests of auditory processing. Methods: The present study is observational, descriptive, transversal and prospective. There were selected 60 subjects aged between 18 and 35 years, presenting normal hearing, parted by the presence (study group) and absence (control group) of the complaint of speech comprehension. The fulfilled evaluations were Masking-level Difference MLD, Random Gap Detection Test RGDT and Brainstem Auditory Evoked Potential (BAEP) using speech and click stimuli. Results: Both behavioral tests demonstrated no significant differences between groups, whereas both tests presented more normal responses than altered ones in both groups. The BAEP-click and speech produced more altered results in the study group and did not presented correlation between each other and the behavioral tests between the groups. Conclusion: It was possible to investigate the functionality of the auditory pathway in brainstem level through the BAEP with speech stimuli in subjects presenting or not speech comprehension complaints and the difference between the groups was not statistically significant, for both BAEP and behavioral tests of auditory processing.